Non-aqueous electrolyte and lithium ion battery thereof

By using trimethylsilyl phosphate and alkenyl-containing succinic anhydride compounds in the non-aqueous electrolyte in lithium-ion batteries, the insufficient circulation and storage performance of lithium-ion batteries under high temperature conditions was solved, and the problem of insufficient circulation and storage performance of lithium-ion batteries was achieved. Higher battery stability and energy density extend the battery life.

CN119170871AActive Publication Date: 2024-12-20ZHUHAI SMOOTHWAY ELECTRONICS MATERIALS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411292386.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-20
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have insufficient cycling and storage performance under high temperature conditions, especially the catalytic reaction activity of high nickel positive electrodes and the volume expansion of silicon-carbon negative electrodes limit the energy density and range of the battery.

Method used

Using a non-aqueous electrolyte containing trimethylsilyl phosphate and alkenyl-containing succinic anhydride compounds, the synergistic action of these two substances forms an interface protective layer to reduce the dissolution of active nickel and oxygen, and reduce the Electrolyte oxidation improves the stability of the positive electrode, and reduces the risk of lithium-ion interface analysis through double bond polymerization, reduces the internal resistance of the battery, and improves battery circulation and storage performance.

Benefits of technology

It significantly improves the high-temperature circulation and high-temperature storage performance of lithium-ion batteries, reduces the battery's gas production and negative electrode interface expansion, extends the battery's service life, and improves the battery's stability and energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170871A_ABST
    Figure CN119170871A_ABST
Patent Text Reader

Abstract

The invention provides a non-aqueous electrolyte and a lithium ion battery thereof. Wherein the non-aqueous electrolyte comprises a lithium salt, an organic solvent and an additive, the additive comprises trimethylsilyl phosphate and a compound A as shown in a formula I or a formula II, and R1 and R2 are selected from C1-C12 alkyl groups. The additive comprises the trimethylsilyl phosphate and the alkenyl-containing succinic anhydride compound, through the synergistic effect of the two substances, the stability of the positive electrode material can be effectively improved, the problem of volume expansion of a negative electrode interface is solved, and then the effect of improving the high-temperature storage performance and the high-temperature cycle performance of the lithium ion battery is achieved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a non-aqueous electrolyte and a lithium ion battery thereof. Background Art

[0002] Pure electric vehicles (BEV) have become the future development trend of the automotive industry, and the driving range has become an obstacle to the development of current electric vehicles. In order to solve the range anxiety, the main direction of improvement on the material side is to use single cells with higher energy density, such as high nickel positive electrodes and silicon-carbon negative electrodes. The electrolyte, as the only liquid substance in the battery, plays a very important role in the energy density of the two materials. For example: 1. How to improve the volume expansion caused by the silicon-carbon negative electrode from the electrolyte side, 2. How to alleviate the high catalytic reaction activity of the high nickel positive electrode during the cycle from the electrolyte side, etc. These problems restrict the development of high energy density electrolytes and also limit the development of high energy density batteries.

[0003] Therefore, it is urgent to develop an effective electrolyte to solve the problems existing in the prior art. Summary of the invention

[0004] The object of the present invention is to provide a non-aqueous electrolyte and a lithium ion battery thereof, wherein the non-aqueous electrolyte comprises trimethylsilyl phosphate and alkenyl-containing succinic anhydride compounds, and the synergistic effect between the two substances can effectively improve the stability of the positive electrode material, thereby improving the high temperature cycle performance of the battery, and at the same time can alleviate the problem of volume expansion of the negative electrode interface, thereby improving the high temperature storage performance of the lithium ion battery.

[0005] To achieve the above object, the present invention provides a non-aqueous electrolyte, comprising a lithium salt, an organic solvent and an additive, wherein the additive comprises trimethylsilyl phosphate and a compound A as shown in Formula 1 or Formula 2:

[0006]

[0007] Wherein, R1 and R2 are selected from C1 to C12 alkyl groups.

[0008] Compared with the prior art, the present invention introduces alkenyl-containing succinic anhydride compounds and trimethylsilyl phosphate into the non-aqueous electrolyte. The alkenyl-containing succinic anhydride compounds contain succinic anhydride, which can form a good interface protection layer on the surface of the positive electrode material, thereby reducing the dissolution of active nickel and active oxygen, reducing the probability of the electrolyte being oxidized, thereby improving the stability of the positive electrode side, and further improving the cycle stability of the battery. At the same time, the double-bonded alkenyl can undergo double-bond polymerization reaction at the negative electrode interface. Compared with a single alkenyl substance, the alkenyl has a relatively large anhydride functional group, which reduces The polymerization degree is increased, thereby reducing the overall battery internal resistance (compared to substances containing alkenyl groups alone), reducing the risk of lithium precipitation at the negative electrode interface, and matching trimethylsilyl phosphate. Trimethylsilyl phosphate itself can effectively reduce the battery interface resistance. When the two are used at the same time, the hydrogen adsorption between the P=O bond of trimethylsilyl phosphate and the C=O in the anhydride is used to reduce the acidic substances generated by the use of C=O in the anhydride alone, significantly improving the stability of the non-aqueous electrolyte, and reducing the effect of the acid value on the interface film components, thereby achieving the effect of improving the battery storage stability. Therefore, the non-aqueous electrolyte can maintain a stable SEI film under long-term circulation conditions, inhibit the oxidative decomposition of the non-aqueous electrolyte, thereby reducing the decomposition and gas production of the organic electrolyte, thereby improving the high-temperature cycle and high-temperature storage performance of the lithium-ion battery and alleviating the expansion of the negative electrode interface volume.

[0009] As a preferred technical solution, R1 and R2 are independently selected from C1 to C6 straight-chain or branched alkyl groups. Among them, C1 to C6 alkyl groups specifically refer to alkyl groups with carbon atoms between 1 and 6, and these alkyl groups can be straight-chain alkyl groups or branched alkyl groups. Further, C1 to C6 straight-chain alkyl groups specifically refer to alkyl groups with carbon atoms connected in a straight line, such as methyl (CH3-), ethyl (CH3CH2-), propyl (CH3CH2CH2-), butyl (CH3CH2CH2CH2-), pentyl (CH3(CH2)3-) and hexyl (CH3(CH2)4-). C1 to C6 branched alkyl groups refer to alkyl groups with branches on carbon atoms on the basis of straight-chain alkyl groups. For example, isopropyl ((CH3)2CH-), isobutyl (CH3CH(CH3)CH2-), sec-butyl (CH3CH2CH(CH3)-), tert-butyl ((CH3)3C-), etc.

[0010] As a preferred technical solution, the compound A of the present invention is selected from at least one of compounds 1 to 6:

[0011]

[0012] As a preferred technical solution, the mass percentage of compound A of the present invention in the non-aqueous electrolyte is 0.05% to 2.0%. Further, the mass percentage of compound A in the non-aqueous electrolyte is about 0.1% to 1.0%, about 0.1% to 0.5%. As an example, the mass percentage of compound A in the non-aqueous electrolyte can be, but is not limited to, 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%.

[0013] As a preferred technical solution, the mass percentage of trimethylsilyl phosphate (TMSP) in the non-aqueous electrolyte of the present invention is 0.05% to 2.0%. Further, the mass percentage of trimethylsilyl phosphate in the non-aqueous electrolyte is about 0.1% to 1.5%, about 0.5% to 1.0%. As an example, the mass percentage of trimethylsilyl phosphate in the non-aqueous electrolyte can be but is not limited to 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%.

[0014] As a preferred technical solution, the lithium salt of the present invention is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiN(CF3SO2)2), lithium bis(oxalatoborate) (C4BLiO8), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (C2BF2LiO4), lithium difluorobis(oxalatophosphate) (LiDFBP) and lithium bis(fluorosulfonyl)imide (LiFSI).

[0015] As a preferred technical solution, the mass percentage of the lithium salt in the non-aqueous electrolyte of the present invention is 5% to 20%. Further, the mass percentage of the lithium salt in the non-aqueous electrolyte is 6% to 15%. As an example, the mass percentage of the lithium salt in the non-aqueous electrolyte may be, but is not limited to, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%.

[0016] As a preferred technical solution, the organic solvent of the present invention is selected from at least one of carbonate organic solvents, carboxylate organic solvents and ether organic solvents.

[0017] Specifically, carbonate organic solvents may be, but are not limited to, linear carbonates, cyclic carbonates, and fluorocarbons. For example, carbonate organic solvents include, but are not limited to, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), pentylene carbonate, vinylene carbonate (VC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), etc.; carboxylate organic solvents include, but are not limited to, fluorocarboxylates, butyl acetate (n-Ba), γ-butyrolactone (γ-Bt), propyl propionate (n-PP), ethyl propionate (EP), and ethyl butyrate (Eb), etc.; ether organic solvents include, but are not limited to, fluoroethers, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, methyltetrahydrofuran, diphenyl ether, and crown ethers, etc.

[0018] As a preferred technical solution, the mass percentage of the organic solvent in the non-aqueous electrolyte of the present invention is 60% to 90%. Further, the mass content of the organic solvent in the non-aqueous electrolyte is 70% to 85%. As an example, the mass percentage of the organic solvent in the non-aqueous electrolyte may be, but is not limited to, 60, 65%, 70%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%.

[0019] Another aspect of the present invention provides a lithium-ion battery, comprising a positive electrode material and a negative electrode material, and also comprising the above-mentioned non-aqueous electrolyte.

[0020] As a preferred technical solution, the positive electrode material of the present invention is selected from nickel-cobalt-manganese oxide material, and the chemical formula of the nickel-cobalt-manganese oxide material is LiNi x Co y Mn (1xy) M z O2, 0.6≤x≤0.9, x+y<1, 0≤z<0.08, M is one of Al, Mg, Zr and Ti. Preferably x=0.6, y=0.2, M is Zr, z=0.03, or x=0.8, y=0.1, M is Zr, z=0.02.

[0021] As a preferred technical solution, the negative electrode material of the present invention is selected from silicon-carbon negative electrode material. Specifically, the weight percentage of silicon to carbon in the silicon-carbon negative electrode material can be 1:9. DETAILED DESCRIPTION

[0022] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0023] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0024] Example 1

[0025] (1) Preparation of non-aqueous electrolyte: In a glove box filled with nitrogen (O2 <2 ppm, H2O <3 ppm), ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) were mixed in a weight ratio of EC:DEC:EMC = 1:2:1 to prepare 83.8 g of an organic solvent, followed by adding 0.2 g of compound 1 and 1 g of TMSP, dissolving them, stirring them thoroughly, then adding 15 g of lithium hexafluorophosphate, and mixing them evenly to obtain a non-aqueous electrolyte.

[0026] (2) Preparation of positive electrode: LiNi 0.8 Co 0.1 Mn 0.1 Zr 0.03 O2, adhesive PVDF and conductive agent SuperP are evenly mixed in a mass ratio of 97:1:2 to form a lithium-ion battery positive electrode slurry with a certain viscosity. The mixed slurry is coated on both sides of an aluminum foil, and then dried and rolled to obtain a positive electrode sheet.

[0027] (3) Preparation of negative electrode: Silicon-carbon negative electrode material (10 wt.% Si) is mixed with conductive agent SuperP, thickener CMC, and adhesive SBR (styrene-butadiene rubber latex) in a mass ratio of 96:1:1:2 to make a slurry, mix them evenly, apply the mixed slurry on both sides of the copper foil, dry and roll-press to obtain the negative electrode sheet.

[0028] (4) Preparation of lithium-ion batteries: The positive electrode sheets, separators and negative electrode sheets are stacked to form a square battery cell, which is packaged with a polymer and filled with the above-prepared lithium-ion battery non-aqueous electrolyte. After the steps of formation and capacity separation, a lithium-ion battery with a capacity of 1400 mAh is manufactured.

[0029] The non-aqueous electrolyte formulations of Examples 1-13 and Comparative Examples 1-6 are shown in Table 1. The steps of preparing the electrolyte and making the battery in Examples 2-13 and Comparative Examples 1-6 are the same as those in Example 1.

[0030] Table 1 Electrolyte components of various embodiments and comparative examples

[0031]

[0032]

[0033] The lithium ion batteries prepared in Examples 1 to 13 and Comparative Examples 1 to 6 were subjected to high temperature cycle performance tests, high temperature storage performance tests and thickness expansion rate tests, respectively. The specific test conditions are as follows, and the test results are shown in Table 2.

[0034] (1) High temperature cycle performance

[0035] Place the lithium-ion battery in a 45℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge at 2C constant current to a voltage of 4.45V, then charge at 4.45V constant voltage to a current of 0.05C, then discharge at 1C constant current to a voltage of 3.0V, and record the first cycle discharge capacity of the battery as C0. This is one charge and discharge cycle. Then, charge and discharge at 1C / 1C for 300 cycles at 45℃, and record the discharge capacity as C1.

[0036] Capacity retention rate = C1 / C0*100%

[0037] (2) High temperature storage test

[0038] At room temperature (25°C), the lithium-ion battery is charged and discharged at 0.3C / 0.3C (the battery discharge capacity is recorded as C0), the upper limit voltage is 4.45V, and then the battery is charged to 4.45V under 0.3C constant current and constant voltage conditions, and the battery thickness is measured (the thickness is recorded as D0); the battery is placed in a 60°C oven for 30D, taken out and the battery thickness is measured (the thickness is recorded as D1), and the battery is placed in a 25°C environment and discharged at 0.3C, and the discharge capacity is recorded as C1; then the lithium-ion battery is charged and discharged at 0.3C / 0.3C (the battery discharge capacity is recorded as C2), and the capacity retention rate, capacity recovery rate and thickness expansion rate of the lithium-ion battery are calculated using the following formula:

[0039] Capacity retention rate = C1 / C0*100%

[0040] Capacity recovery rate = C2 / C0*100%

[0041] Thickness expansion rate = D1 / D0*100%

[0042] Table 2 Lithium-ion battery performance test results

[0043]

[0044]

[0045] Table 3 Electrolyte acid value stability performance test results

[0046]

[0047]

[0048] From the results in Table 2, it can be seen that based on Comparative Examples 1 to 6, Examples 1 to 13 of the present invention can improve the high-temperature storage and high-temperature cycle performance of high-nickel ternary positive electrode material system batteries under high voltage by using compound A on the basis of TMSP, and can reduce the gas production of the battery. Further, from the comparison of Examples 1 to 6, it can be seen that when compound 6 is used in combination with TMSP, its performance is the best, which may be because the structural functional groups containing side chains affect the degree of polymerization of the double bonds, thereby affecting the film-forming effect of the performance anhydride of the structural material, and then affecting the high temperature performance of the battery and the gas production performance of the battery.

[0049] It can be seen from the test results in Table 3 that when the non-aqueous electrolyte contains both TMSP and compound A, the acid value stability of the electrolyte during storage is significantly improved and maintained at a relatively low level.

[0050] The non-aqueous electrolyte of the present invention comprises alkenyl-containing succinic anhydride compounds and trimethylsilyl phosphate. The alkenyl-containing succinic anhydride compounds can form a good interface protection layer on the surface of the positive electrode material because of the presence of succinic anhydride, thereby reducing the dissolution of active nickel and active oxygen, reducing the probability of the electrolyte being oxidized, thereby improving the stability of the positive electrode side, and further improving the cycle stability of the battery. At the same time, the double-bonded alkenyl can undergo double-bond polymerization reaction at the negative electrode interface. Compared with a single alkenyl substance, the alkenyl has a relatively large anhydride functional group, which reduces the polymerization reaction. degree, thereby reducing the overall battery internal resistance (compared to substances containing alkenyl groups alone), reducing the risk of lithium precipitation at the negative electrode interface, and matching trimethylsilyl phosphate, which itself can effectively reduce the battery interface resistance. When the two are used at the same time, the P=O bond of trimethylsilyl phosphate is used to build hydrogen adsorption between C=O in the acid anhydride, which reduces the acidic substances generated by using C=O in the acid anhydride alone, significantly improving the stability of the non-aqueous electrolyte, and reducing the influence of the acid value on the interface film components, thereby achieving the effect of improving the battery storage stability. Therefore, the non-aqueous electrolyte of the present invention can maintain a stable SEI film under long-term circulation conditions, inhibit the oxidative decomposition of the non-aqueous electrolyte, thereby reducing the decomposition and gas production of the organic electrolyte, thereby improving the high-temperature cycle and high-temperature storage performance of the lithium-ion battery and alleviating the expansion of the negative electrode interface volume.

[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A non-aqueous electrolyte comprising a lithium salt, an organic solvent and an additive, characterized in that: The additive includes trimethylsilyl phosphate and a compound A as shown in Formula 1 or Formula 2: Wherein, R1 and R2 are each independently selected from C1-C12 alkyl groups.

2. The non-aqueous electrolyte according to claim 1, characterized in that The compound A is selected from at least one of compounds 1 to 6:

3. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage of the compound A in the non-aqueous electrolyte is 0.05% to 2.0%.

4. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage of the trimethylsilyl phosphate in the non-aqueous electrolyte is 0.05% to 2.0%.

5. The non-aqueous electrolyte according to claim 1, characterized in that The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisoxalatoborate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium difluorobisoxalatophosphate and lithium bisfluorosulfonyl imide.

6. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage of the lithium salt in the non-aqueous electrolyte is 5% to 20%.

7. The non-aqueous electrolyte according to claim 1, characterized in that The organic solvent is selected from at least one of a carbonate organic solvent, a carboxylate organic solvent and an ether organic solvent.

8. A lithium ion battery comprising a positive electrode material and a negative electrode material, characterized in that: It also includes the non-aqueous electrolyte according to any one of claims 1 to 7.

9. The lithium-ion battery according to claim 8, characterized in that: The positive electrode material is selected from nickel-cobalt-manganese oxide material, and the chemical formula of the nickel-cobalt-manganese oxide material is LiNi x Co y Mn (1xy) M z O2, 0.6≤x≤0.9, x+y<1, 0≤z<0.08, M is one of Al, Mg, Zr and Ti.

10. The lithium ion battery according to claim 8, characterized in that The negative electrode material is selected from silicon-carbon negative electrode materials.

Citation Information

Patent Citations

  • Battery electrolyte additive, electrolyte containing additive and application of electrolyte

    CN109638353A

  • Lithium ion battery electrolyte and lithium ion battery

    CN110828893A

  • Electrolyte and lithium ion battery containing same

    CN115020812A

  • Lithium ion battery electrolyte and lithium ion battery containing same

    CN115172879A

  • Nonaqueous Secondary Battery

    US20210351437A1